2018
DOI: 10.1038/s41598-018-26991-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantile regression analysis of modifiable and non-modifiable drivers’ of blood pressure among urban and rural women in Ghana

Abstract: High blood pressure is an increasingly problematic public health concern in many developing countries due to the associated cardiovascular and renal complications. This study set out to investigate the drivers of blood pressure among urban and rural women using the 2014 Ghana Demographic and Health Survey data. Diastolic blood pressure (DBP) and systolic blood pressure (SBP) were the outcomes of interest. Our findings showed that body mass index (BMI) had a significant positive effect on DBP and SBP in both ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…A study involving institutional older adults in Tunisia also found that hypertension was 80% higher in obese subjects (86.9%) than in subjects with normal BMI [91]. Obesity is a well-recognized driver of hypertension in Africa with obese subjects being up to eight times as likely as those non-obese to have hypertension [86, 92, 93]. In view of the predominant association of overweight/obesity with hypertension and its increasing trend in Africa, there is an opportunity to explore the role of lifestyle interventions on improving the cardiovascular health of older adults [94, 95].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving institutional older adults in Tunisia also found that hypertension was 80% higher in obese subjects (86.9%) than in subjects with normal BMI [91]. Obesity is a well-recognized driver of hypertension in Africa with obese subjects being up to eight times as likely as those non-obese to have hypertension [86, 92, 93]. In view of the predominant association of overweight/obesity with hypertension and its increasing trend in Africa, there is an opportunity to explore the role of lifestyle interventions on improving the cardiovascular health of older adults [94, 95].…”
Section: Discussionmentioning
confidence: 99%
“…The drain associated with hypertension is worsened by poor knowledge, increasing engagement in risk factors, poor medication adherence, lack of prevention resources, and poor healthcare infrastructure for treatment with its impact felt in regions where general literacy including health literacy is noted to be low (Adeloye, 2014 ). Hypertension is also noted to be associated with increasing prevalence of cardiovascular diseases, ischaemic heart diseases, stroke, congestive heart failure, acute myocardial infarction, peripheral vascular disease and renal failure (Adeoye et al, 2017 ; Akpa et al, 2020 ; Amugsi et al, 2018 ; Anto et al, 2020 ; Appiah et al, 2017 ; Benneh‐Akwasi Kuma et al, 2018 ; Dassah et al, 2019 ; Kodaman, Aldrich, Sobota, Asselbergs, Brown, et al, 2016 ; Kodaman, Aldrich, Sobota, Asselbergs, Poku, et al, 2016 ; Obirikorang et al, 2016 ). Hypertension is also associated with worsening socioeconomic status, increasing healthcare cost to both patients and governments (Abegaz et al, 2017 ; Weldegebreal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension health promotion interventions are mostly targeted to those factors that can be altered through individual efforts-largely referred to as modifiable risk factors [ 33 36 ]. These targets of health promotion intervention incorporate those environmental and social determinants of health that include lifestyle factors like heart-healthy diet [ 37 , 38 ], reduction in sodium and adequate potassium [ 35 38 ], increased physical activity [ 37 ], reduction in overweight and obesity [ 39 42 ] as well as increased knowledge on hypertension risk factors [ 11 , 35 38 , 43 ]. The specific target of these modifiable risk factors, especially among the entire population, has been shown in this study to be critical if significant gains are going to be made in the total control of hypertension.…”
Section: Discussionmentioning
confidence: 99%